Uji Efektivitas Ekstrak Daun Awar-Awar (Ficus Septica Burm F) untuk Menghambat Pertumbuhan Jamur Phytophthora infestans Penyebab Penyakit Hawar Daun Tomat - NOVA SULIYANTI SIANTURI; DEWA NGURAH SUPRAPTA; NI WAYAN SUNITI (Agrotrop : Journal on Agriculture Science, 2023)
Effectiveness of Awar-Awar (Ficus septica Burm F) Leaf Extract to Inhibit the Growth of the Fungus Phytophthora infestans that Causes Tomato Late Blight. Tomato late blight caused by the fungus Phytophthora infestans is one of the main diseases affecting tomato production in the world. Therefore, it needs to be controlled in an environmentally friendly way, one of which is by using vegetable pesticides. Awar-awar leaves are one of the plants whose extracts can be used as vegetable fungicides. This study aimed to examine the potency of awar-awar leaf extract against P. infestans which causes late blight of tomatoes. MIC test and colony test used 10 extract concentrations, namely 0.1%; 0.2%; 0.3%; 0.4%; 0.5%; 0.6%; 0.7%: 0.8%; 0.9%; 1.0% and control. The in vivo test used 8 extract concentrations, namely 0.3%; 0.4%; 0.5%; 0.6%; 0.7%: 0.8%; 0.9%; 1.0% and control. The results showed that the Minimum Inhibitory Concentration (MIC) of awar-awar leaf extract to suppress the growth of P. infestans was 0.3%, which means that it is suitable for use as a vegetable pesticide. Colony test results showed that awar-awar leaf extract was able to inhibit the growth of P. infestans fungal colonies. In vivo awar-awar leaf extract inhibits the growth of fungal colonies and the occurrence of infection, and can be fungicidal to suppress the growth of P. infestans. Extract concentration of 1% can suppress tomato leaf damage by P. infestans by 75.90%.